Oral cannabidiol did not impair learning and memory in healthy adults - Hanna H. Gebregzi; Joanna S. Zeiger; Jeffrey P. Smith; Libby Stuyt; Luann Cullen; Jim Carsella; Daniel C. Rogers; Jordan Lafebre; Jennah Knalfec; Alfredo Vargas; Moussa M. Diawara (Journal of Cannabis Research, 2025)
Abstract Background The effect of oral Cannabidiol (CBD) on interference during learning and memory (L&M) in healthy human volunteers has not been studied. Method A two-arm crossover, randomized, double-blind, placebo-controlled trial was conducted at Colorado State University Pueblo (CSU Pueblo) to evaluate the effects of 246 mg oral CBD on L&M in healthy adults. Among 57 healthy volunteers enrolled, 35 were included in the analyses. For assessment of L&M, Montreal Cognitive Assessment (MOCA) was used to evaluate verbal baseline cognitive function; RAVLT-R tests (List A and List B recalls, Proactive and Retroactive Interference ratios, and Forgetting Speed ratio) were used to evaluate verbal declarative memory; and total prose recall was used to evaluate verbal logical memory. Linear Mixed Models with Bonferroni Corrections were used to compare L&M results between primary outcomes (CBD vs. placebo) and secondary demographic outcomes, with a two-tailed statistical significance of P < 0.05. Results CBD administration did not affect any of the dependent variables measured compared to the placebo group. There were no effects of THC, history of CBD use, or sex on CBD’s modulation of L&M. However, a highly significant interaction effect between treatment groups (CBD vs. placebo) and age of subjects was observed for the PI ratio (P = 0.008; n = 35). Conclusions The results of this study suggest that administration of oral CBD alone does not significantly impair L&M in healthy adults. However, age might influence CBD related modulation of proactive interference during human L&M. Future research involving a larger group of older adults is needed to confirm this potential effect. Trial registration The study was approved by the CSU Pueblo IRB, conducted in accordance with the Declaration of Helsinki, and registered with ClinicalTrials.gov (NCT06074172).